Outcome After Thrombectomy and Intravenous Thrombolysis in Patients With Acute Ischemic Stroke: A Prospective Observational Study. Issue 6 (June 2016) - Minnerup, Jens; Wersching, Heike; Teuber, Anja; Wellmann, Jürgen; Eyding, Jens; Weber, Ralph; Reimann, Gernot; Weber, Werner; Krause, Lars Udo; Kurth, Tobias; Berger, Klaus; Homberg, V.; et al.
Abstract : Background and Purpose—: In patients with ischemic stroke, randomized trials showed a better functional outcome after endovascular therapy with new-generation thrombectomy devices compared with medical treatment, including intravenous thrombolysis. However, effects on mortality and the generalizability of results to routine clinical practice are uncertain. Methods—: In a prospective observational register-based study patients with ischemic stroke treated either with thrombectomy, intravenous thrombolysis, or their combination were included. Primary outcome was the modified Rankin scale score (0 [no symptoms] to 6 [death]) at 3 months. Ordinal logistic regression was used to estimate the common odds ratio as treatment effects (shift analysis). Propensity score matching was applied to compare patients treated either with intravenous thrombolysis alone or with intravenous thrombolysis plus thrombectomy. Results—: Among 2650 recruited patients, 1543 received intravenous thrombolysis, 504 underwent thrombectomy, and 603 received intravenous thrombolysis in combination with thrombectomy. Later time-to-treatment was associated with worse outcomes among patients treated with thrombectomy plus thrombolysis. In 241 pairs of propensity score–matched patients with a proximal intracranial occlusion, thrombectomy plus thrombolysis was associated with improved functional outcome (common odds ratio, 1.84; 95% confidence interval, 1.32–2.57), and reduced mortality (15% versus 33%; P <0.0001) compared with intravenous thrombolysis alone. Results were similar in various sensitivity analyses accounting for missing outcome data and different analytic methods. Conclusions—: Results from this large prospective registry show that also in routine clinical care thrombectomy plus thrombolysis compared with thrombolysis alone improved functional outcome and reduced mortality in patients with ischemic stroke. Earlier treatment was associated with better outcomes. Abstract : Supplemental Digital Content is available in the text.